IMPLEMENTASI PERLINDUNGAN HUKUM WISATAWAN DALAM MENGIKUTI PAKET RAFTING WHITEWATER DI KNB HOLIDAY MEDAN - Padriadi Wiharjokusumo1; Novita Romauli Saragih2 (Akademi Pariwisata Darma Agung, 2020)
Implementation of Legal Protection of Tourists, will not be separated who is responsible for an act to whom the act can be accounted for and whether anyone who commits an act where the consequences of the act can cause harm to people, can be accounted for by the maker. This research examines the implementation of legal protection of tourist in following whitewater rafting package at KNB Holiday Medan. This research was conducted through anempirical legal approach. The data source of this research was gained from the field study. Then analyzed using the qualitative analysis which depicts and dissects the significant information.The conclusion of this research wasthat the implementation of KNB Holiday’s responsibility towards tourists in the event of things that are detrimental to consumers in practice is responsible for the extent of their profession or agreements that have been agreed with consumers of service users, namely strict liability against strict professional liability. Keywords:implementation, responsibility, KNB Holiday.